THE EFFECTIVENESS OF SUPPLY CHAIN MANAGEMENT PRACTICES ON MANUFACTURING MICRO, SMALL AND MEDIUM ENTERPRISES (MSME) IN LUSAKA: A CASE OF MANDEVU AND KALINGALINGA MARKETS - Demberere, Jeffrina; Kasongo, Richard Mwale (Global Journal of Purchasing and Procurement Management, 2021)
Purpose: The purpose of this study was to find out the state of supply chain management within MSME's in Zambia by investigating the Supply Chain Management (SCM) practices, its benefits and challenges using some selected manufacturing micro, small-medium enterprises in Mandevu and Kalingalinga markets of Lusaka. Methodology: The study used descriptive research design and chose questionnaire as the tool for data collection. Purposive sampling technique was employed to obtain information from both the management and staff of the MSMEs. One hundred (100) questionnaires were distributed to the respondents. The obtained data were then analysed using the descriptive method. Results: The study found out that the manufacturing MSME sector appreciates good supply chain management practices, but does not practise it. The study discovered that the sector has not established long term relationships with its customers and suppliers. The sector was found to face several challenges which threaten its long term growth and survival, the most worrying challenges being the lack of financial resources, failure to practice continuous quality improvement, low integration of process technologies and forecasting challenges. The study also revealed that when implemented SCM practices deliver a number of benefits to the MSMEs. For example, increased response to the customer, cost-cutting on service delivery, improved information sharing and improved capacity to offer after-sale services. It is evident that MSMEs would perform well if supply chain management activities are improved. This, however, can be accomplished, if the MSMEs engage in strategic partnerships, customer relationship, high level of information sharing, information quality, as well as continuous quality improvement. Unique contribution to theory, practice and policy: The study could be replicated in other industry sectors of the economy and also in other developing countries to help build on the body of knowledge.